Preparation method and application of RAFT (reversible addition-fragmentation chain transfer) polymerization modified graphene oxide
Patent Information
- Application Number
- CN202411410374.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
Graphene oxide is poorly dispersed in high alkali and high salt cement slurry, resulting in a decrease in the fluidity of cement-based materials, affecting its enhanced toughening effect, and will lead to a decrease in mechanical properties when it exceeds a certain amount.
The preparation method of RAFT polymerized modified graphene oxide is formed by the treatment of graphite powder, NaNO3, KMnO4, H2SO4 and other materials, and is incorporated into cement mortar to improve its dispersion and stability. .
The compressive strength and flexural strength of cement-based materials are significantly improved. When the doping amount is 0.01 to 0.10%, the compressive strength is increased by 5.83 to 21.56%, the flexural strength is increased by 3.77 to 15.58%, and the cement hydration history and Hydration product structure.
Smart Images

Figure CN119285257A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene oxide modification, and specifically relates to a preparation method and application of RAFT polymerization modified graphene oxide. Background Art
[0002] As a basic material, cement-based materials are widely used in industrialization and urbanization. Traditional cement-based materials have defects in their internal microstructures, such as holes and microcracks, which make them poor in crack resistance, low in tensile and compressive strength, and prone to cracks or even breakage, which seriously affects the safety and service life of cement-based materials.
[0003] Studies have found that nanotechnology can be used to regulate the microstructure of cement hydration products, provide a large number of nucleation sites for cement hydration, and thus improve the mechanical properties of cement-based materials. Compared with 0D and 1D nanomaterials, the two-dimensional interface interaction between 2D graphene oxide (GO) and cement matrix can effectively regulate the microstructure of cement-based material hydration products, accelerate cement hydration, refine pore structure, and hinder crack development. The addition of a small amount of GO can effectively regulate the cement hydration process and the structure of hydration products, and significantly improve the mechanical properties of cement-based materials; however, when GO exceeds a certain amount, due to the large number of oxygen-containing functional groups on the surface of GO, such as -OH, -COO-, and -COOH, it is easy to react with Ca in alkaline cement paste. 2+ Combined with GO, forming aggregates, resulting in a decrease in its mechanical and rheological properties. Some studies have found that mixing GO with polycarboxylate water reducer can improve the agglomeration of GO in alkaline cement paste, but it will delay the cement hydration process. Therefore, the bottleneck problem of GO modification technology needs further research to solve. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the fact that the GO is poorly dispersed in high-alkali and high-salt cement paste and forms aggregates, the fluidity of cement-based materials is reduced, thereby affecting the strengthening and toughening effect of GO on cement-based materials. In view of the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing RAFT polymerization-modified graphene oxide.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] Graphite powder, NaNO3 and concentrated H2SO4 were stirred in an ice bath, KMnO4 was added, stirred, deionized water was added, stirred, H2O2 was added, cooled and allowed to stand, the precipitate was centrifuged, washed with water, freeze-dried and ground into powder to obtain GO;
[0009] GO and N,N-dimethylformamide were mixed, DCMA, DMAP and DCC were added, stirred and centrifuged, and the precipitate was washed with CH2Cl2 until the supernatant was colorless, vacuum dried and ground into powder to obtain GR;
[0010] GR and N,N-dimethylformamide were mixed, OEGA and AIBN were added, and N2 was continuously bubbled to allow grafting reaction. The product was washed with CH2Cl2, centrifuged until the supernatant was colorless, and freeze-dried to obtain GE.
[0011] GE and N,N-dimethylformamide were mixed, KH-570 and AIBN were added, and N2 was continuously bubbling, and the reaction was carried out at high temperature. The product was washed with CH2Cl2, centrifuged until the supernatant was colorless, and freeze-dried to obtain RAFT polymerization modified graphene oxide.
[0012] As a preferred scheme of the preparation method of RAFT polymerization modified graphene oxide described in the present invention, wherein: the mass ratio of the graphite powder to NaNO3 is 1-2:1, the mass ratio of the graphite powder to KMnO4 is 1:3-3.5, the concentration of the graphite powder in concentrated H2SO4 is 35-40 g / L, and the volume ratio of the deionized water to concentrated H2SO4 is 1-1.5:1.
[0013] As a preferred embodiment of the method for preparing RAFT polymerization modified graphene oxide described in the present invention, the concentration of GO in N,N-dimethylformamide is 5 to 10 g / L.
[0014] As a preferred embodiment of the method for preparing RAFT polymerization modified graphene oxide of the present invention, the molar ratio of DCMA, DMAP and DCC is 2-8:1-4:3-9, and the concentration of DMAP in N,N-dimethylformamide is 6.3-8.4 g / L.
[0015] As a preferred embodiment of the method for preparing RAFT polymerization modified graphene oxide described in the present invention, the mass ratio of GR to OEGA is 14-15:1, and the concentration of GR in N,N-dimethylformamide is 5-10 g / L.
[0016] As a preferred embodiment of the method for preparing RAFT polymerization-modified graphene oxide described in the present invention, the concentration of GE in N,N-dimethylformamide is 5 to 10 g / L.
[0017] As a preferred embodiment of the method for preparing RAFT polymerization modified graphene oxide described in the present invention, the concentration of KH-570 in N,N-dimethylformamide is 112.5-150 g / L, and the concentration of AIBN in N,N-dimethylformamide is 0.53-1.5 g / L.
[0018] As a preferred scheme of the preparation method of RAFT polymerization modified graphene oxide described in the present invention, wherein: the temperature of the grafting reaction is 70-75°C, the time is 8-10 hours, and N2 is continuously introduced during the reaction; the time of the high temperature reaction is 8-24 hours, the temperature is 85-90°C, and N2 is continuously introduced during the reaction.
[0019] Another object of the present invention is to overcome the deficiencies of the prior art and provide RAFT polymerization-modified graphene oxide obtained by the preparation method of RAFT polymerization-modified graphene oxide.
[0020] Another object of the present invention is to overcome the shortcomings of the prior art and provide an application of RAFT polymerization modified graphene oxide obtained by the preparation method of RAFT polymerization modified graphene oxide, wherein: the RAFT polymerization modified graphene oxide is applied to cement-based composite materials, and when the RAFT polymerization modified graphene oxide is added to cement mortar in an amount of 0.01 to 0.10%, compared with the original cement mortar, the compressive strength is increased by 5.83 to 21.56%, and the flexural strength is increased by 3.77 to 15.58%.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention synergizes the modification effects of GO and block copolymer (including polysilane block), that is, constructs a block copolymer grafted on the surface of GO, thereby improving the dispersibility and stability of GO in alkaline cement slurry.
[0023] (2) The present invention uses RAFT polymerization on the GO surface to graft polyether-polysilane block copolymer onto the GO surface to synthesize GO-g-POE-b-PMPS, revealing the rules and mechanism of GO-g-POE-b-PMPS in regulating the cement hydration process and the structure of hydration products, and clarifying the interfacial interaction between GO sheets and CSH.
[0024] (3) Based on the optimization of cement matrix hydration and interfacial behavior by GO-g-POE-b-PMPS, this paper applies GO-g-POE-b-PMPS to cement-based composites and explores the influence of GO-g-POE-b-PMPS on the structure and properties of cement-based composites. The modified GO can improve the agglomeration problem of GO in cement slurry.
[0025] (4) In the present invention, the compressive and flexural strengths of cement with a GO-g-POE-b-PMPS doping content of 0.03% increase at the fastest rate; the compressive and flexural strengths of cement with a GO-g-POE-b-PMPS doping content of 0.04% are the best. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0027] Figure 1 This is the synthesis route of GO-g-POE-b-PMPS in Example 1 of the present invention.
[0028] Figure 2 FT-IR graph of GO, GE and KGE in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] Raw materials used in the embodiments of the present invention:
[0033] DMF, N,N-dimethylformamide, AR;
[0034] DMAP, 4-dimethylaminopyridine, AR;
[0035] DCC, tricyclohexylcarbodiimide, AR;
[0036] DCMA, 2-(dodecylthiocarbonylthio)-2-methylpropanoic acid, AR;
[0037] AIBN, azobisisobutyronitrile, AR;
[0038] KH-570, 3-methacryloyloxypropyltrimethoxysilane, AR;
[0039] The above reagents were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0040] OEGA, polyethylene glycol methyl ether acrylate, Mn=480 g / mol, AR, purchased from Sigma-Aldrich.
[0041] The water used in the experimental process of the present invention is deionized water.
[0042] Example 1
[0043] This embodiment provides a preparation method for RAFT polymerization of graphene oxide modification, the synthesis route is as follows Figure 1 shown.
[0044] 1.Synthesis of GO
[0045] 4.0g graphite powder, 2.0g NaNO3 and 100.0mL concentrated H2SO4 were added to 500mL, the mass ratio of graphite powder to NaNO3 was 2:1, the concentration of graphite powder in concentrated H2SO4 was 40g / L, and stirred at low speed for 1.5h in an ice bath. 12.0g KMnO4 was slowly added, the mass ratio of graphite powder to KMnO4 was 1:3, stirred at 35℃ for 2h, 150mL H2O was slowly added, the volume ratio of deionized water to concentrated H2SO4 was 1.5:1, heated to 95℃ and stirred for 60min, 9mL H2O2 was added, cooled to room temperature, and placed for 24h. The precipitate was centrifuged three times at 8000rpm with 10% HCl, then washed with water several times until the pH was about 7, freeze-dried, and ground into powder to obtain GO.
[0046] 2. Synthesis of GO-RAFT(GR)
[0047] 0.5g GO and 50mL DMF were added to a 150mL three-necked flask, the concentration of GO in N,N-dimethylformamide was 10g / L, stirred at room temperature for 15min, and ultrasonicated for 20min. 2.742g DCMA (RAFT agent), 0.420g DMAP and 1.830g DCC were added, the molar ratio of the three was 2:1:3, the concentration of DMAP in N,N-dimethylformamide was 8.4g / L, and stirred at room temperature for 24h. The above product was centrifuged at 6000rpm and washed several times with CH2Cl2 until the supernatant was colorless, and vacuum dried at 45℃ for 6h to obtain GO-RAFT, which was ground into powder to obtain GR.
[0048] 3. Synthesis of GO-g-POE(GE)
[0049] 0.5g GR and 50ml DMF were added to a 150mL three-necked flask, GO concentration was 10g / L, stirred at room temperature for 15min, and ultrasonicated for 25min. 7.50g OEGA and 35mg AIBN (0.7g / L) were added, the mass ratio of GR to OEGA was 14:1, N2 was passed for 30min (continuous bubbling), the temperature was raised to 75℃ under low-speed stirring, the reaction was continued for 8h (continuous N2), the product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain GE.
[0050] 4. Synthesis of GO-g-POE-b-PMPS(KGE)
[0051] 0.5g GE and 50ml DMF were added to a 150mL three-necked flask, the GE concentration was 10g / L, stirred at room temperature for 15min, and ultrasonicated for 25min. 7.50g KH-570 (concentration was 150g / L) and 35mg AIBN (concentration was 0.7g / L) were added, N2 was passed for 30min (continuous bubbling), and the temperature was raised to 90℃ under low-speed stirring, and the reaction was continued for 18h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0052] Figure 2 FT-IR images of GO, GE and KGE. 3205cm -1 and 1395cm -1 The stretching vibration and bending vibration of OH on the GO sheet are 1216cm -1 The COC vibration peak of the epoxy group appears at 1061 cm -1 The peak at 1719 cm-1 is the stretching vibration peak of the alkoxy C-OH group. -1 Corresponding to the C=O stretching vibration of carboxyl and carbonyl groups, 1636 cm -1 The corresponding C=C stretching vibration is 1059cm -1 The peak corresponds to CO stretching vibration, 3215cm -1 The peak at 2950cm corresponds to OH stretching vibration. -1 、1442cm -1 The peak at 1216 cm corresponds to the CH stretching vibration of the polyether chain. -1 The peak corresponds to the asymmetric stretching vibration of ester CO, 1713 cm -1 The C=O stretching vibration peak at 1077 cm -1 The CO stretching vibration peak at 1081 cm -1 The stretching vibration absorption peaks of Si-OC and SO-Si bonds appeared at 2902 and 2839 cm-1 It is -CH3 and -CH2 in KH-570.
[0053] Example 2
[0054] This embodiment provides a preparation method for RAFT-polymerized graphene oxide modification.
[0055] 1.Synthesis of GO
[0056] Same as step 1 in Example 1.
[0057] 2. Synthesis of GO-RAFT(GR)
[0058] 0.5gGO and 100mL DMF were added to a 150mL three-necked flask, with a GO concentration of 5g / L, stirred at room temperature for 15min, and ultrasonicated for 20min. 4.113gDCMA (RAFT agent), 0.63gDMAP and 2.745gDCC were added, with a molar ratio of 8:4:9, a DMAP concentration of 6.3g / L, and stirred at room temperature for 24h. The above product was centrifuged at 6000rpm and washed several times with CH2Cl2 until the supernatant was colorless, and vacuum dried at 45℃ for 6h to obtain GO-RAFT, which was ground into powder to obtain GR.
[0059] 3. Synthesis of GO-g-POE(GE)
[0060] 0.5g GR and 100ml DMF were added to a 150mL three-necked flask, GR concentration was 5g / L, stirred at room temperature for 15min, and ultrasonicated for 25min. 11.25g OEGA and 53mg AIBN were added, the mass ratio of GR to OEGA was 15:1, AIBN concentration was 0.53g / L, N2 was passed for 30min (continuous bubbling), and the temperature was raised to 75℃ under low-speed stirring, reacted for 8h (continuous N2), the product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain GE.
[0061] 4. Synthesis of GO-g-POE-b-PMPS(KGE)
[0062] 0.5g GE and 100ml DMF were added to a 150mL three-necked flask, with a GE concentration of 5g / L. The mixture was stirred at room temperature for 15min and ultrasonicated for 25min. 11.25g KH-570 (112.5g / L) and 53mg AIBN (0.53g / L) were added, and N2 was passed through for 30min (continuous bubbling). The mixture was heated to 90°C with low-speed stirring, and reacted for 18h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0063] Example 3
[0064] This embodiment provides a preparation method for RAFT-polymerized graphene oxide modification.
[0065] Steps 1 to 3 are all based on Example 1, and the synthesis of GO-g-POE-b-PMPS (KGE) in step 4 is adjusted to:
[0066] 0.5g GE and 100ml DMF were added to a 150mL three-necked flask, with a GE concentration of 5g / L. The mixture was stirred at room temperature for 15min and ultrasonicated for 25min. 11.25g KH-570 (112.5g / L) and 53mg AIBN (0.53g / L) were added, and N2 was passed through for 30min (continuous bubbling). The mixture was heated to 90°C with low-speed stirring, and reacted for 8h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0067] Example 4
[0068] This embodiment provides a preparation method for RAFT-polymerized graphene oxide modification.
[0069] Steps 1 to 3 are all based on Example 1, and the synthesis of GO-g-POE-b-PMPS (KGE) in step 4 is adjusted to:
[0070] 0.5g GE and 50ml DMF were added to a 150mL three-necked flask, with a GE concentration of 5g / L. The mixture was stirred at room temperature for 15min and ultrasonicated for 25min. 7.50g KH-570 (150g / L) and 35mg AIBN (0.7g / L) were added, and N2 was passed through for 30min (continuous bubbling). The mixture was heated to 60°C with low-speed stirring, and reacted for 18h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0071] Example 5
[0072] This embodiment provides a preparation method for RAFT-polymerized graphene oxide modification.
[0073] Steps 1 to 3 are all based on Example 1, and the synthesis of GO-g-POE-b-PMPS (KGE) in step 4 is adjusted to:
[0074] 0.5g GE and 50ml DMF were added to a 150mL three-necked flask, with a GE concentration of 5g / L. The mixture was stirred at room temperature for 15min and ultrasonicated for 15min. 7.50g KH-570 (150g / L) and 35mg AIBN (0.7g / L) were added, and N2 was passed through for 30min (continuous bubbling). The mixture was heated to 90°C with low-speed stirring, and reacted for 24h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0075] Example 6
[0076] Steps 1 to 3 are all based on Example 1, and the synthesis of GO-g-POE-b-PMPS (KGE) in step 4 is adjusted to:
[0077] 0.5g GE and 50ml DMF were added to a 150mL three-necked flask, with a GE concentration of 5g / L. The mixture was stirred at room temperature for 15min and ultrasonicated for 15min. 7.50g KH-570 (150g / L) and 75mg AIBN (1.5g / L) were added, and N2 was passed through for 30min (continuous bubbling). The mixture was heated to 90°C with low-speed stirring, and reacted for 18h (continuous N2 passing). The product was washed with CH2Cl2, centrifuged at 6000rpm until the supernatant was colorless, and freeze-dried to obtain KGE.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that steps 2, 3, and 4 are omitted, and RAFT polymerization grafting modification is not performed. Step 1 is the same as Example 1, and graphene oxide is synthesized.
[0080] Comparative Example 2
[0081] In the process of synthesizing GE and KGE in this comparative example, nitrogen was not introduced, and the other steps were the same as those in Example 1.
[0082] The polymer material KGE was obtained.
[0083] The properties of the materials in Examples 1-6 and Comparative Examples 1 and 2 were measured.
[0084] The mud mortar uses benchmark cement and standard sand with a water-cement ratio of 0.35. The compressive strength of cement mortar is tested in accordance with the requirements of GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The dosage of polymer KGE is 0.03%. Table 1 is a comparison of the compressive strength of cement mortar after doping with the materials prepared in Examples 1-6 and Comparative Examples 1 and 2, where the blank sample is cement mortar without doping with other substances.
[0085] Table 1 Comparison of compressive strength of cement mortar with different dopants
[0086]
[0087] It can be seen from Table 1 that after the polymers prepared in Examples 1-6 are mixed with cement, the compressive strength of the cement is improved compared with that in Comparative Example 1, indicating that after the polymer KGE synthesized by graphene oxide grafting blocks is mixed with cement-based materials, its dispersibility in the cement matrix can be improved, thereby improving the compressive strength of the hardened cement mortar. Compared with Examples 2-6, the compressive strength of the hardened cement mortar is most significantly improved under the conditions of Example 1.
[0088] The compressive strength of the material in Comparative Example 2 is lower than that of the blank group, indicating that KGE needs to create an oxygen-free environment during the synthesis process.
[0089] The polymer KGE of Comparative Example 1 and Example 1 was added to cement mortar to explore the effects of different KGE dosages on the compressive strength and flexural strength of the hardened cement mortar, as shown in Table 2, where the blank group was cement mortar without any other substances.
[0090] Table 2 Comparison of compressive strength and flexural strength of cement mortar at different KGE dosages
[0091]
[0092] It can be seen from Table 2 that, compared with the blank group, the addition of GO and KGE can increase the compressive and flexural strength of the hardened cement mortar with the increase of curing time. When the amount of polymer KGE added to the cement mortar is 0.01-0.10%, compared with the blank group, the compressive strength of the cement mortar is increased by 5.83-21.56%, and the flexural strength is increased by 3.77-15.58%.
[0093] Compared with adding GO, adding KGE can better improve the dispersion of nanosheets in cement paste. With the increase of curing age, the compression and flexural strength of cement mortar are enhanced more obviously. After adding 0.03wt% KGE, the compressive strength of the samples cured for 3 days, 7 days and 28 days increased by 14.3%, 18.6% and 21.7% respectively, and the flexural strength increased by 9.5%, 11.8% and 14.3% respectively compared with the blank samples.
[0094] Comprehensive evaluation of multiple indicators shows that when the dosage reaches 0.04wt% KGE, the flexural strength and compressive strength of cement mortar begin to increase slowly; when the dosage reaches 0.10wt% KGE, the flexural strength and compressive strength of cement mortar begin to decrease. The compressive and flexural strength of cement with 0.03% KGE dosage increases fastest; the compressive and flexural strength of cement with 0.04% KGE dosage is the best.
[0095] In summary, the present invention synergizes the modification effects of GO and block copolymers (including polysilane blocks), that is, constructs a block copolymer grafted on the GO surface, thereby improving the dispersibility and stability of GO in alkaline cement slurry; by RAFT polymerization on the GO surface, the polyether-polysilane block copolymer is grafted on the GO surface to synthesize GO-g-POE-b-PMPS, revealing the rules and mechanism of GO-g-POE-b-PMPS in regulating the cement hydration process and the structure of the hydration products, and clarifying the interfacial interaction between GO sheets and CSH. Based on the optimization of cement matrix hydration and interface behavior by GO-g-POE-b-PMPS, the present invention applies GO-g-POE-b-PMPS to cement-based composites, explores the influence of GO-g-POE-b-PMPSE on the structure and performance of cement-based composites, and finds that the modified GO can improve the agglomeration problem of GO in cement slurry; the compressive and flexural strength of cement with a GO-g-POE-b-PMPS doping amount of 0.03% increases the fastest; the compressive and flexural strength of cement with a GO-g-POE-b-PMPS doping amount of 0.04% is the best.
[0096] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing RAFT polymerization-modified graphene oxide, characterized in that: include, Graphite powder, NaNO3 and concentrated H2SO4 were stirred in an ice bath, KMnO4 was added, stirred, deionized water was added, stirred, H2O2 was added, cooled and allowed to stand, the precipitate was centrifuged, washed with water, freeze-dried and ground into powder to obtain GO; GO and N,N-dimethylformamide were mixed, DCMA, DMAP and DCC were added, stirred and centrifuged, and the precipitate was washed with CH2Cl2 until the supernatant was colorless, vacuum dried and ground into powder to obtain GR; GR and N,N-dimethylformamide were mixed, OEGA and AIBN were added, and N2 was continuously bubbled to allow grafting reaction. The product was washed with CH2Cl2, centrifuged until the supernatant was colorless, and freeze-dried to obtain GE. GE and N,N-dimethylformamide were mixed, KH-570 and AIBN were added, and N2 was continuously bubbling, and the reaction was carried out at high temperature. The product was washed with CH2Cl2, centrifuged until the supernatant was colorless, and freeze-dried to obtain RAFT polymerization modified graphene oxide.
2. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The mass ratio of the graphite powder to NaNO3 is 1-2:1, the mass ratio of the graphite powder to KMnO4 is 1:3-3.5, the concentration of the graphite powder in concentrated H2SO4 is 35-40 g / L, and the volume ratio of the deionized water to concentrated H2SO4 is 1-1.5:
1.
3. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The concentration of GO in N,N-dimethylformamide is 5-10 g / L.
4. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The molar ratio of the DCMA, DMAP and DCC is 2-8:1-4:3-9, and the concentration of the DMAP in N,N-dimethylformamide is 6.3-8.4 g / L.
5. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The mass ratio of the GR to OEGA is 14-15:1, and the concentration of the GR in N,N-dimethylformamide is 5-10 g / L.
6. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The concentration of the GE in N,N-dimethylformamide is 5-10 g / L.
7. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The concentration of KH-570 in N,N-dimethylformamide is 112.5-150 g / L, and the concentration of AIBN in N,N-dimethylformamide is 0.53-1.5 g / L.
8. The method for preparing RAFT polymerization-modified graphene oxide according to claim 1, characterized in that: The temperature of the grafting reaction is 70-75°C, the time is 8-10 hours, and N2 is continuously introduced during the reaction; the time of the high-temperature reaction is 8-24 hours, the temperature is 85-90°C, and N2 is continuously introduced during the reaction.
9. RAFT polymerization-modified graphene oxide obtained by the method for preparing RAFT polymerization-modified graphene oxide according to any one of claims 1 to 8.
10. The use of RAFT polymerization modified graphene oxide according to claim 9, characterized in that: The RAFT polymerization-modified graphene oxide is applied to prepare cement-based composite materials. When the RAFT polymerization-modified graphene oxide is added to cement mortar in an amount of 0.01-0.10%, the compressive strength is increased by 5.83-21.56% and the flexural strength is increased by 3.77-15.58% compared with the original cement mortar.